Remoted balbot - Lee, Kong Haur (2010)
In this age of fast changing technology, robots become part and parcel of our lives and yet it undergoes research and development in order to perform various of tasks. However, two-wheeled balancing robot nowadays could be considered as a challenging task for the robot hobbyists. For this project, Brain Board and Balance Board are the two most important elements for the two-wheeled balancing mobile robot system in order to make it has the capable of balancing upright of two wheels, as well as to interface or communicate effectively with the wireless PS2 controller via the aid of PSC28A I/O converter. Hence, the software of Brain Board Code Editor provided can be used to develop our own navigation system which will then be loaded into the ATMEGA32 microcontroller on the Brain Board. Finally, the two-wheeled balancing robot can be navigated wirelessly by using the remote control of wireless PS2 controller. By then, analysis will be done in order to analyze the mobile robot in both of the balancing mode and also exploring mode.